(untitled) (Research, Society and Development, 2021)
Analyze the learning style preferences of elementary school students and teachers. This is a qualitative research of the exploratory study type. 193 students and 19 elementary school teachers from two public schools in Alegrete-RS effectively participated in the study. The David Kolb Learning Styles Inventory (LSI) was used for data collection. It was observed that the predominant learning styles in the profile of the students were Assimilating (n=89; 46,25%) and Convergent (n=61; 31,73%). It was noted that the Convergent learning style predominates the profile of teachers (n=9; 47,37%) respondents. It noticed that there is a more even distribution between the learning styles of teachers than the styles of students. It is understood that the predominant teaching styles of teachers are compatible with students’ learning styles. It was noted that there are several learning and teaching profiles. It was understood that the learning styles of teachers, which they are based on to teach, encompass different learning styles of their students. From this, it is understood that the profile of teachers makes it possible to explore the different ways that students tend to learn. It is believed that identifying learning styles is a pedagogical strategy that, combined with the use of innovative methodologies on teaching, has the potential to help in the effectiveness of educational interventions. Including the quality of the teaching and learning process.